Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $f(x) = x^{4} - 1$ and $g(x)= x^{4}- 4$.

Let $V$ be the vector space consisting of real polynomials of degree less than or equal to $3$.

Let $T:V \longrightarrow V$ be the map such that for $h \in V$, $T(h)$ is the remainder of the Euclidean division of $fh$ by $g$.

Show that $T$ is a linear map.

I thought I could start by proving that $T(0) = 0$? How would I proceed after that?

share|improve this question
5  
After that, prove $T(a+b)=T(a)+T(b)$ and $T(ra)=rT(a), r\in \mathbb{R}$. That's assuming $V$ is a vector space of real polynomials-you didn't specify. –  Kevin Carlson Oct 17 '12 at 22:11

1 Answer 1

Think the point in this exercise is to remember the definition of the Euclidian division.

Namely, you should remember that, given polynomials $p, q \neq 0$ there always exist polynomials $c, r$ such that

$$ p = qc + r \qquad \text{with} \quad r = 0 \quad \text{or}\quad \mathrm{deg}(r) < \mathrm{deg}(q) \ . $$

Moreover, the quotient $c$ and the remainder $r$ are unique verifying this equation with this condition.

Right?

So, let's try to prove that $T(h + h') = T(h) + T(h')$, for instance. By definition of $T$, we have:

\begin{eqnarray*} fh &= gc_h + T(h) &\qquad \text{with} \quad T(h) = 0 \quad \text{or}\quad \mathrm{deg}(T(h)) < \mathrm{deg}(g) \\ fh' &= gc_{h'} + T(h') &\qquad \text{with} \quad T(h') = 0 \quad \text{or}\quad \mathrm{deg}(T(h')) < \mathrm{deg}(g) \end{eqnarray*}

Now, let's add up both equations:

$$ f(h+h') = g (c_h + c_{h'}) + T(h) + T(h') \ . $$

This looks familiar, doesn't it?

Indeed, with we think for a moment, we conclude that we also have

$$ T(h) + T(h') = 0 \quad \text{or} \quad \mathrm{deg}(T(h) + T(h')) < \mathrm{deg}(g) \ , $$

haven't we? But these are exactly the conditions that, by definition, the reminder $T(h+h')$ verifies:

$$ f(h+h') = g c_{h+h'} + T(h + h') \qquad \text{with} \quad T(h +h') = 0 \quad \text{or} \quad \mathrm{deg}(T(h) + T(h')) < \mathrm{deg}(g) \ . $$

But, remember that this equation and condition defined both the quotient and the remainder uniquely. Hence we must have

$$ T(h+h') = T(h) + T(h') \ . $$

(And also $c_{h+h'} = c_h + c_{h'}$, but they didn't ask us to prove that.)

Ok, so now try to prove

$$ T(\lambda h) = \lambda T(h) $$

and you're done.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.